2005
DOI: 10.1103/physreva.71.033623
|View full text |Cite
|
Sign up to set email alerts
|

First- and second-order superfluid–Mott-insulator phase transitions of spin-1 bosons with coupled ground states in optical lattices

Abstract: We investigate the superfluid-Mott-insulator quantum phase transition of spin-1 bosons in an optical lattice created by pairs of counterpropagating linearly polarized laser beams, driving an Fg = 1 to Fe = 1 internal atomic transition. The whole parameter space of the resulting two-component Bose-Hubbard model is studied. We find that the phase transition is not always second order as in the case of spinless bosons, but can be first order in certain regions of the parameter space. The calculations are done in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 5 publications
5
37
0
Order By: Relevance
“…Metastable Mott-insulator (MMI) and meta-stable superfluid (MSF) phases emerge due to the spin barrier, and lead to first-order SF-MI phase transitions (see Figs. 1(a) and 1(c)) [14,16,17]. When 3D lattices are ramped up and down, hysteresis is expected across the phase transitions (i.e., different transition lattice depth u c ).…”
mentioning
confidence: 99%
“…Metastable Mott-insulator (MMI) and meta-stable superfluid (MSF) phases emerge due to the spin barrier, and lead to first-order SF-MI phase transitions (see Figs. 1(a) and 1(c)) [14,16,17]. When 3D lattices are ramped up and down, hysteresis is expected across the phase transitions (i.e., different transition lattice depth u c ).…”
mentioning
confidence: 99%
“…In addition, both the MI phases and SF-MI transitions of spin-1 bosons have been intensively studied [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The ferromagnetically interacting system is essentially similar to spinless bosons, whereas the antiferromagnetically interacting system exhibits rich physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…This conjecture has been confirmed by the density matrix renormalization group (DMRG) [22] and quantum Monte Carlo simulation (QMC) [24,25] in one dimension (1D). However, mean-field (MF) studies beyond the perturbation theory [17][18][19] have shown a possible first-order SF-MI transition of the BH model for a weak antiferromagnetic interaction, such as U 2 /U 0 ≃ 0.04, which corresponds to 23 Na. This first-order transition in 1D has also been revealed by a QMC study [24].…”
Section: Introductionmentioning
confidence: 99%
“…These experimental developments have stimulated extensive study of related theoretical models [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In particular, the behavior of spin-1 bosons in a double-well potential can be described by a variant of the two-site BoseHubbard Hamiltonian [25] including spin-dependent interactions [11,23] that affect physical properties of the system.…”
Section: Introductionmentioning
confidence: 99%